SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMAAN PENGAJAR TILAWATIL QURAN MENGGUNAKAN METODE PROFILE MATCHING - Isma Auli Mahrani; Rainah Rainah; Afrisawati Afrisawati; Parini Parini (LPPM STMIK Royal Kisaran, 2023)
Abstract: The teacher of tilawatil quran is an important figure for quran students. In this context, the selection of the right teacher plays a key role in ensuring the success and effectiveness of learning the recitation of the quran. The selection system for teaching recitation of the quran at Baitul Quran Al-Haq Aek Songsongan is currently subjective, causing several problems because there is no decision support system in the process of selecting the eligibility of accepting teachers. The purpose of this study is to apply the profile matching method in selecting the eligibility of accepting teachers at Baitul Quran Al-Haq Aek Songsongan which can assist the foundation in selecting teachers based on established criteria, so that it can increase effectiveness and objectivity in selecting the eligibility of accepting teachers at Baitul Quran Al-Haq Aek Songsongan. Profile matching itself is a decision making method with propositions that have ideal views and results obtained through ranking. The results of this study through the process of calculating the profile matching method, obtained A4 = Adinda Pratiwi as an alternative that occupies the first rank of the five alternatives to become prospective teachers. Keywords: Decision Support System; Profile Matching; Teacher Abstrak: Pengajar tilawatil quran merupakan sosok penting bagi para pelajar quran. Dalam konteks ini, pemilihan pengajar yang tepat memainkan peranan kunci dalam memastikan keberhasilan dan efektivitas pembelajaran tilawatil quran. Sistem pemilihan pengajar tilawatil quran di Baitul Quran Al-Haq Aek Songsongan saat ini bersifat subjektif sehingga menimbulkan beberapa masalah karena belum adanya sistem pendukung keputusan dalam proses pemilihan kelayakan penerimaan pengajar. Adapun tujuan penelitian ini untuk menerapkan metode profile matching dalam memilih kelayakan penerimaan pengajar pada Baitul Quran Al-Haq Aek Songsongan yang dapat membantu pihak yayasan dalam memilih pengajar berdasarkan kriteria yang ditetapkan, sehingga dapat meningkatkan efektifitas dan objektifitas dalam pemilihan kelayakan penerimaan pengajar di Baitul Quran Al-Haq Aek Songsongan. Profile matching itu sendiri merupakan metode pengambilan keputusan dengan proposisi yang memiliki nilai pandangan yang ideal dan hasil yang diperoleh melalui perankingan. Hasil dari penelitian ini melalui proses perhitungan metode profile matching, diperoleh A4 = Adinda Pratiwi sebagai alternatif yang menduduki rangking pertama dari lima alternatif yang menjadi calon pengajar. Kata Kunci: Profile Matching; Sistem Pendukung Keputusan; Pengajar